An archaeological experiment with early medieval glass bead production in an open hearth – the results - Krzyżanowska, Marta; Frankiewicz, Mateusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
The aim of the experimental research was to verify the hypothesis of glass bead production in an open hearth. In this case, data from archeological excavations in Ribe, where the remains of “glass” hearths were discovered, was utilised. The experiment involved the forming of the hearth, where a clay nozzle in the shape of a loom weight was placed in the centre. The air was pumped into the hearth using bellows equipped with a separate air circulation system. The results of the research indicate that, thanks to such a construction and thanks to the process of charcoal sieving, the manufacturing of simple and more complex glass beads is simple and the hearths themselves are quite effective.